Social Criticsm in The Short Story “Lailatu Zifaf (Wedding Night)” By Najib Kailani - Muhammad Thoriqussuud; Malik Fahad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Abstract: Every literary work created conveys certain messages about social life from the author's point of view, these messages may be the author's way of addressing real social problems. Social criticism contributed to clarifying this issue. Social criticism will show readers that every literary work is a mirror of social and cultural life.The purpose of this research is to describe the forms of social criticism in the short story